THE EFFECT OF DIFFERENT TYPE OF SERA ON MATURATION RATE OF BUFFALO FOLLICULAR OOCYTES - MISTRY, C N; DHAMI, A J; SUTHAR, V S; JOSHl, C G; RANK, D N (The Indian Journal of Animal Reproduction, 2023)
A total of 1409 follicular oocytes were recovered by slicing method from 456 ovaries of Surtibuffaloes collected from the local abattoir. The object was to assess the effect of different categories ofbuffalo sera (20%, with natural hormones) in relation to BSA (0.6%, Sigma, supplemented with 10 IU/mlof eCG - Folligon and 5 IU/ml of hCG - Chorulon, lntervet) on in vitro maturation (IVM) of oocytes inTCM-199 medium. The sera were obtained locally from different categories of animals, viz., fetal bovineserum (FBS, Gibco), neonatal buffalo serum (NBS), oestrus buffalo serum (OBS), post-oestrus buffaloserum (POSS), and anoestrus buffalo serum (AnBS) and processed further for heat inactivation in thelaboratory. The oocyte recovery rate was 3.09 per ovary. The average oocyte recovery of grade A, gradeBand grade C was 1.02, 1.22 and 0.85, respectively. The maturation rate in presence of POBS, AnBS,FBS, NBS and OBS, each at 20 % level in TCM-199 medium, was found to be 64.63, 54.55, 70.63,60.48 and 78.16 per cent, respectively, as against 84.00 per cent with 0.6 % BSA supplemented withhormones. The culture medium containing oestrus buffalo serum (OBS) yielded significantly higher(P
Keywords: Buffalo; Oocyte; Abattoir ovaries; Slicing; Different type of sera; In vitro maturation